RELATIONSHIPS OF THE IMPLEMENTATION OF A 3M PLUS PROGRAM AND THE EXISTENCE OF AEDES AEGYPTI LARVAE TOWARDS THE NUMBER OF DENGUE FEVER CASES IN THE PUBLIC HEALTH CENTER OF TIGO BALEH BUKITTINGGI, WEST SUMATERA, INDONESIA - Alhamda, Syukra (YCAB Publisher & IAKMI SULTRA, 2017)
Background: Dengue fever in Tigo baleh Bukittinggi community is one of the infectious diseases resulting in serious health problems. Understanding the factors associated with the disease is necessity.Objective: To determine the relationships of the implementation of 3M plus program and the existence of Aedes aegypti larvae towards the number of dengue fever cases in the public health center of Tigo Baleh Bukittinggi, West Sumatera, Indonesia.Methods: This was a case control study conducted between January and December 2016 in the Public Health Center of Tigo Baleh Bukittinggi. There were 78 samples recruited by total sampling, with 39 were assigned in the case and control group. House index (HI) and Container index (CI) were used to measure the presence of Aedes aegypti larvae. The implementation of 3M plus program was measured using questionnaire developed by the researcher. Chi Square was performed for data analysis. Result: Findings showed that house index value was 43.6% and container index was 17.9%. The presence of larvae at home contributes to 24 (61.5%) cases of DHF in the case group and 10 (25.6%) cases in the control group. Poor implementation of the program contributes to 27 (69.2%) cases in the case group and 17 (43.6%) in the control group. Chi square test showed p 0.040 (<0.05) for the 3M plus implementation and p 0.03 (<0.05) for the presence of Aedes aegypti. Conclusion: There were significant associations between the implementation of 3m plus program and the existence of Aedes aegypti larvae towards the number of dengue fever cases in the public health center of Tigo Baleh Bukittinggi, West Sumatera, Indonesia. It is suggested that the community should do more efforts to prevent the occurrence of DHF through mosquito nest eradication, such as the implementation of 3M Plus and sanitation efforts, and pay attention to any places that potentially become a breeding ground for Aedes aegypti mosquitoes.